Misdiagnosed with spinal infection instead of SAPHO syndrome: a case report and literature review - Wang, Shuai; Wan, Shiyong; Chang, Zhengqi (Frontiers in Immunology, 2025)
This article reports a case of SAPHO syndrome misdiagnosed as spinal infection, detailing the clinical manifestations, laboratory tests, and imaging features of the patient. Through a review of the literature, common confounding factors and reasons for misdiagnosis in the diagnostic process of this disease are summarized. Comprehensive analysis of multiple related studies reveals that detailed medical history collection, advanced imaging examinations (such as ECT), and multidisciplinary consultations play a decisive role in making a correct diagnosis. Furthermore, the literature shows that the treatment for SAPHO syndrome is fundamentally different from spinal infection, with the former mainly relying on anti-inflammatory regulation, bone protective agents, and immune modulation therapy, rather than the indiscriminate use of antibiotics. This report aims to remind clinicians to maintain a high level of vigilance when facing spinal lesions, and to compare and summarize the latest advances in diagnosis and treatment, providing a reference for improving the level of diagnosis and treatment in the future.